Upaya Pemberdayaan Bisnis Grosir “Jaya Mandiri” Melalui Pelatihan Dan Pendampingan Digitalisasi UMKM Yang Diadakan Oleh Narasumber.id - Carissa Ruth Malinda; Sumainah Fauziah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Empowerment of the wholesale business "Jaya Mandiri" through training and mentoring for digitalization of MSMEs is a form of student support for Indonesian MSMEs which was learned and applied while participating in the MSIB "Digitalization of MSMEs" activities held by Resource Persons.id. In the current digital era, technology has a very important role in helping MSMEs to optimize their market and business potential. However, implementing digitization is not an easy thing for some MSMEs, there are still many people who have limited knowledge and access to technology. One solution that can be done is by providing training and assistance to MSMEs as held by Resource Persons.id. With the aim of expanding market share and increasing the ability of MSME owners regarding the use of digital technology.